Stress and Coping Among Emergency Unit Healthcare Workers in Tanjungpinang During Covid-19 Pandemic - Muhammad Rizki; Eka Kurnia Saputra; Octojaya Abriyoso; Indra Widianto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
COVID-19 is a global health problem. The number of positive cases keep increasing globally towards the end of 2020, including in Indonesia. This is a challenging situation for the healthcare workers who provide services to the patient without knowing whether the patients infected by COVID-19 or not, especially for those who work in emergency unit of the hospital. This study aims to explore the stressors and coping strategies among emergency unit healthcare workers in Tanjungpinang, Indonesia. The sample was taken from the emergency unit of Raja Ahmad Tabib Kepulauan Riau Regional Public Hospital as the only referral hospital in Tanjungpinang. Data was collected through interview and then analyze by using thematic analysis approach. The result shows that the source of stress that the emergency unit healthcare workers feel during Covid-19 pandemic is the fear of contacting the disease, fear of infecting family members, as well as negative perceptions from the public. As for the coping methods, it was found out that the emergency unit healthcare workers adhere to health protocol, adding insight on Covid-19 related issues, performing religious activities, adopting healthier lifestyle, seeking social support, and doing relaxing activities in the spare time.